Effectiveness of Radioiodine Therapy for Graves' Hyperthyroidism: A Quality-of-Life Assessment - Fauzi, Machfud; Prajitno, Jongky Hendro; Prabowo, Gwenny Ichsan; Novida, Hermina (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: Graves' disease, an autoimmune disorder characterized by hyperthyroidism, is commonly managed through radioactive iodine therapy, antithyroid drugs, and thyroidectomy. Previous reports suggest that individuals undergoing radioactive iodine therapy exhibit superior overall quality of life and satisfaction compared to those opting for alternative therapeutic modalities. This study systematically reviewed evidence on the effectiveness of radioiodine therapy for Graves' hyperthyroidism, specifically emphasizing its impact on patients' quality of life. Methods: A systematic review was conducted on studies evaluating the quality of life of adult patients with Graves’ hyperthyroidism following radioiodine therapy. A literature search was carried out utilizing the PubMed, ScienceDirect, and Sage Journals online databases. The search results were screened according to the eligibility criteria for inclusion in a narrative synthesis. Results: The search yielded 203 items, of which four articles fulfilled the eligibility criteria and were included in the review. radioiodine therapy demonstrated improvements in the quality of life of patients with Graves' disease compared to other therapeutic modalities or no treatment at all. Enhancement in quality of life was observed across various scales, encompassing physical symptoms (goiter, hyperthyroidism, eye symptoms, and hypothyroidism), psychological symptoms (depression and anxiety), functioning and well-being (fatigue, cognitive impairment, and emotional vulnerability), and participation (social life disruptions, daily life interference, and cosmetic complaints). Conclusion: Findings concerning quality of life underscore the long-term effectiveness of radioiodine therapy as a preferred intervention for Graves' disease, contributing valuable insights for clinical decision-making.   Highlights: 1. This systematic review comprehensively synthesizes research findings regarding the impact of radioiodine therapy on the long-term quality of life of patients with Graves’ hyperthyroidism compared to surgery or antithyroid medication. 2. The findings suggest that radioiodine therapy offers improvement in the quality of life, which may be indicated by physical and psychological symptoms, functioning, well-being, and participation.